FREEDOM OF POLITICAL IN CONDITIONS OF SOCIAL POLARIZATION: PHYCHO-LEGAL ASPECTS OF MASS BEHAVIOR - MELENKO, OKSANA; KARVATSKА, SVITLANA (Ehrlich's Journal, 2025)
The article analyzes the freedom of political expression as a legal phenomenon in the context of social polarization, taking into account its impact on the formation of mass behavior characterized by conflict potential and radical political narratives. The right to freedom of political expression is defined as a fundamental element of democratic society and constitutional order. It is noted that this right ensures citizens’ ability to articulate their positions, exchange ideas, and contribute to public discourse. At the same time, under conditions of social polarization, this right acquires controversial manifestations, particularly in the form of mass behavior. The study conceptualizes the phenomenon of mass behavior as activated by political mobilization, allowing it to be interpreted in terms of the radicalization of public communication. It is emphasized that political statements during election campaigns become a tool for influencing the electorate, stimulating emotionally charged reactions. Given that, under conditions of information manipulation, freedom of speech may substitute rational choice with impulsive sentiments, it is concluded that such processes create a dangerous threshold between democratic order and legal chaos. Mass behavior, fueled by political narratives, generates risks of social confrontation. The lack of a clear boundary between organized and spontaneous forms of political activity contributes to the disruption of public order. Propaganda and political rhetoric appeal to basic emotions and national identity, intensifying the effects of social aggression. This undermines critical thinking, which is essential for the functioning of democracy. As a result, freedom of expression loses its emancipatory potential and turns into a tool of mass mobilization inclined toward destructive political activity. The relevance of the study is determined by the need to rethink the mechanisms of legal regulation in the field of political communication. There is a pressing need to develop an effective legal balance between the protection of freedom of speech and the safeguarding of information security. Only such an approach can ensure democratic resilience and national unity. In this context, the right to freedom of political expression must not only be protected but also structured in accordance with the challenges of social polarization.